PENCEGAHAN DAN PENGENDALIAN INFEKSI NOSOKOMIAL DI RUMAH SAKIT - Heriyati Heriyati; Hatisah .; Ayu Astuti (Jurnal Pendidikan Kesehatan, 2020)
Infectious diseases related to health care are the latest health related problems in various countries of the world, including Indonesia. The incidence of nosocomial infections or commonly referred to as Healthcare Associated Infection or HAIs in 2018 by Majene Regional Hospital received Decubitus is 10 percent, IDO 10.6 percent, Plebitis 47.8 percent. While the target that must be achieved by Majene Hospital is Decubitus is 10 percent, IDO 2 percent, Plebitis 1 percent. Majene Regency Regional General Hospital. This type of research is quantitative research with cross sectional research. Data were processed univariate and bivariate using the chi square test. Results obtained There was a dispute between respondents who answered against and controlling HAI with a significance level of p equal 0.00 or p is smaller than 0.05. means there is a relationship between the level of knowledge of infection protection and control in Majene Regency Regional General Hospital.